Oral health-related quality of life and oral manifestations of Syrian children with congenital heart disease: a case-control study - Shouq Sharar Bsesa; Samir Srour; Mayssoon Dashash (BMC, 2023)
Abstract Background There was an immense need for studies evaluating the oral health status of Syrian children with congenital heart disease (CHD) and its impact on their quality of life. No contemporary data are available. The objective of this study was to investigate oral manifestations and oral health-related quality of life (OHRQoL) of children with CHD and compare them with healthy controls aged 4-12 years. Methods A case-control study was undertaken. A total of 200 patients with CHD and 100 healthy children belonging to the same patient's family were included. Decayed, missed, and filled permanent teeth index (DMFT) and decayed, missed, and filled primary teeth index (dmft), Oral Hygiene Index (OHI), Papillary Marginal Gingivitis Index (PMGI), and dental abnormalities were recorded. The Arabic version of the Child Oral Health-Related Quality of Life Questionnaire (COHRQoL, 36-item) which was divided into 4 different domains (Oral Symptoms, Functional Limitations, Emotional Well-Being, Social Well-Being) were studied. Chi-square test and independent- t-test were used to perform statistical analysis. Results CHD patients experienced more periodontitis, dental caries, poor oral health, and enamel defects. The dmft mean was significantly higher in CHD patients than in healthy children (5.245 vs. 2.660, P < 0.05). No significant difference was found between patients and controls in the DMFT Mean (P = 0.731). There was a significant difference between CHD patients and healthy children in the mean of the OHI (5.954 vs. 1.871, P < 0.05), and PMGI (1.689 vs. 1.170, P < 0.05). CHD patients have significantly higher enamel opacities (8% vs. 2%) and hypocalcification (10.5% vs. 2%) than controls. Also, the 4 COHRQoL domains, showed significant differences between CHD children and controls. Conclusions Evidence about the oral health and COHRQoL of children with CHD was provided. Further preventive measures are still required to improve the health and quality of life of this vulnerable group of children.